Protests against U.S. military base policy in Asia persuasion and its limits - Kawato, Yuko (Studies in Asian security, 2015)
The US maintains hundreds of external military bases spread across 40 countries worldwide. Using case studies from Japan, South Korea, and the Philippines, Kawato (research fellow, Asia Center, France) works to first show why, and over what issues, protests occur. He then moves to explain why some protests succeed and others fail, articulating a range of policy concessions from major to limited to symbolic.